Efektivitas Kontrak Lisensi Teknologi Hak Cipta Film Dalam Melindungi Kekayaan Intelektual Industri Perfilman Indonesia - Hapsari, Crescentia Viola Priscilla Audra; Lie, Gunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The rapid growth of Indonesia's film industry has created an urgent need for intellectual property protection, particularly through technology-based copyright licensing contracts for films. However, the dynamics of digital distribution and film piracy pose significant legal challenges, especially in ensuring the effectiveness of licensing contracts as protective instruments. This study aims to identify the effectiveness of technology licensing contracts in protecting film copyrights within the framework of national regulations, examine implementation barriers, and offer academic and practical recommendations. The analysis found that film industry actors often face various obstacles, including unclear contract clauses, ineffective dispute resolution mechanisms, and low legal awareness among industry practitioners. Furthermore, there is a gap between existing legal provisions and their enforcement on the ground that weakens copyright protection. Therefore, the study recommends strengthening licensing contract clauses, optimizing dispute resolution mechanisms, and enhancing legal education for industry actors to ensure optimal protection of film copyrights. These findings are expected to contribute to improving the governance of technology licensing contracts, making them more responsive to the challenges of intellectual property protection in the digital era.